The influence of design parameters of rotary dryer on sunflower seeds drying - Yakobchuk, Roman (My University, 2014)
In order to improve the drying of sunflower seeds in the apparatus of the rotary type, it is appropriate to model processes in this devices using computer simulation software. Materials and methods. Simulation of sunflower seeds drying was based on the finite element method using the software package Flow Vision (company "TUSYM") and mathematical and statistical methods. Results. Mathematical models were obtained that show the dependence of pressure of coolant (air) in the drying chamber of rotary dryer on the rate of the coolant, the open cross-sectional area of the gas distributor plate and its resistance, the dependence of duration of sunflower seeds drying on fill factor of the drying chamber and its volume as well as the final material moisture content. The equilibrium distribution of the coolant pressure in the drying chamber of rotary dryer was obtained. It provides a constant height of the fluidized bed of sunflower seeds and quality of its drying. The design of rotary dryer was improved by providing the tangential supply of coolant and installing a spiral partition under gas distribution grid, which allows to uniformly distribute the coolant in the drying chamber. Conclusion. The drying process of sunflower seeds in a rotating dryer was improved. It is advisable to use the experimental result when choosing the mode of drying at the design stage of drying equipment.
Keywords: sunflower; drying; rotary; сушіння; соняшник; ротор; подсолнух; сушка; кафедра технологічного обладнання та комп’ютерних технологій проектування